A review on converting plastic wastes into clean hydrogen via gasification for better sustainability - Midilli, Adnan; Kucuk, Haydar; Haciosmanoglu, Murat; Akbulut, Ugur; Dincer, Ibrahim (WILEY, 2022)
This review paper focuses on converting plastic wastes into clean hydrogen via gasification for better sustainability. In this regard, various aspects of hydrogen production from plastic wastes are discussed and comparatively evaluated, including the state-of-the-art and comparative evaluation, environmental and economical dimensions, global warming aspects, policies and strategies, a case study including energetic and exergetic performance evaluations, challenges and opportunities, and future directions possibly in the area. Additionally, this paper outlines what contributions it makes to the current literature about hydrogen production from plastic wastes by using gasification technologies. Moreover, this paper provides a detailed case study indicating exergetic sustainability aspects for hydrogen production from plastic wastes by applying plasma gasification whose data are taken from the literature. As a result of this case study, some exergetic sustainability indicators are studied for evaluation and comparison purposes. The exergetic sustainability index is found to be decreasing from 0.77 to 0.41 with the fact that exergetic efficiency drops from 0.43 to 0.28 while the environmental impact factor rises from 1.29 to 2.41 with the increase of waste exergy ratio from 0.56 to 0.70. Furthermore, plasma co-gasification can be recommended as an environmentally-benign solution for clean hydrogen production from plastic wastes. Highlights Plastic wastes is an important source of hydrogen. Gasification can efficiently be deployed for hydrogen production from plastic wastes. In order to evaluate potential gasification techniques, energetic, economic, environmental, and sustainability aspects should be considered. Plasma gasification appears to be more efficient and effective solution over other methods for higher amount of hydrogen production from plastic wastes.
Keywords: environmental impact; environmental management; sustainability; exergy; gasification; hydrogen; plasma gasification; plastic wastes; MUNICIPAL SOLID-WASTE; CATALYTIC AIR GASIFICATION; FLUIDIZED-BED GASIFICATION; COAL PLASMA GASIFICATION; BIOMASS GASIFICATION; STEAM GASIFICATION; SYNGAS PRODUCTION; SEWAGE-SLUDGE; LEATHER RESIDUES; 2-STAGE GASIFIER; Energy & Fuels; Nuclear Science & Technology